Evaluating Guideline‐recommended Pain Medication Use Among Patients with Newly Diagnosed Fibromyalgia. Issue 8 (7th October 2015) - Halpern, Rachel; Shah, Sonali N.; Cappelleri, Joseph C.; Masters, Elizabeth T.; Clair, Andrew
Abstract: Objectives: To compare pain medication treatment changes across cohorts of newly diagnosed patients with fibromyalgia (FM) treated with guideline‐recommended medications or opioids. Methods and Design: Retrospective claims data analysis examined adult commercial health plan members newly diagnosed with FM (initial diagnosis = index date) from January 2008 to February 2012. Patients had 6‐month pre‐index and 12‐month postindex periods and received pain medication within 6 months postindex; cohorts were based on the first postindex medication. Guideline‐recommended medication cohorts were anti‐epileptic drug (AED), serotonin–norepinephrine reuptake inhibitor (SNRI), selective serotonin reuptake inhibitor (SSRI), and tricyclic antidepressant (TCA). Short‐acting and long‐acting opioid (SAO, LAO) cohorts were also identified. Pairwise comparisons with the SAO cohort were conducted. Cox proportional hazards regressions modeled the likelihood of receiving guideline‐recommended therapy. Results: The final sample was 96, 175 patients (mean age 47.3 years; 72.5% female), distributed into SAO (57%), SSRI (22%), AED (10%), SNRI (6%), TCA (3%), and LAO (2%) cohorts. The SAO cohort had the most discontinuation (49% vs. 6% to 22%, P < 0.01) and the least augmentation (29% vs. 35% to 50%, P < 0.01). Regression analyses indicated that patients with (vs. without) pre‐index guideline‐recommended medications were 2 to 4 times more likely to receive them postindex. Patients in the opioid cohorts were about half as likely to receive subsequent guideline‐recommended medications. Conclusions: Opioid use was widespread among patients with FM. Once patients received opioids postdiagnosis, the likelihood of receiving guideline‐recommended medications was small. These real‐world results indicate an opportunity may exist for improved FM management using recommended therapies in clinical practice.